Brain Portion Extraction Scheme using Region Growing and Morphological Operation from MRI of Human Head Scans - Somasundaram, K; Mercina, J.Helen; Magesh, S; Kalaiselvi, T (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we propose a brain portion extraction method using single seeded region growing technique and morphological operations. Segmentation requires initial seed point selection, which increases computational cost and execution time. To overcome these problems a single seeded region growing method for image segmentation is proposed. Starts by selecting a seed point at center pixel within the image as the initial seed and grow regions to extract brain portion in Magnetic resonance image. Brain portion is iteratively grown by comparing all unallocated neighbouring pixels to the region. Finally Morphological operations erosion, dilation, and holes filling are performed to extract the fine brain. The performance of the method is estimated using the Jaccard and Dice similarity coefficients. Proposed method was tested with IBSR of brain images and had accurately segmented the brain regions which are better than the existing methods such as Brain Extraction Tool (BET), Brain Surface Extractor (BSE).